2020
DOI: 10.1111/jpy.13103
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Specific Genes and their Expression in the Life History of the Red Alga Bostrychia moritziana (Ceramiales, Rhodomelaceae)

Abstract: Diverse sex determination mechanisms have been reported in eukaryotes, but little is known about the genetic pathways leading to sex determination in red algae. Sex‐specific genes that could be involved in sex determination and sexual differentiation were investigated in the red alga Bostrychia moritziana by analyzing the transcriptomes of various phases including males, females, and tetrasporophytes. Sex dominantly expressed genes which showed >10‐fold difference between sexes was isolated using comparative R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The development of microsatellite-based markers, such as RAPD primers and ddRAD-seq variants, requires library construction and screening large numbers of primer sets, which are time-consuming and laborious steps (Lipinska et al 2015). Our approach for identifying genes with sex-specific expression based on comparisons with genome information for E. siliculosus can be performed using RNA-seq data for female and male strains, without whole genome data, and can be applied to non-model organisms (e.g., Shim et al 2021;Nishitsuji et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of microsatellite-based markers, such as RAPD primers and ddRAD-seq variants, requires library construction and screening large numbers of primer sets, which are time-consuming and laborious steps (Lipinska et al 2015). Our approach for identifying genes with sex-specific expression based on comparisons with genome information for E. siliculosus can be performed using RNA-seq data for female and male strains, without whole genome data, and can be applied to non-model organisms (e.g., Shim et al 2021;Nishitsuji et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach for identifying genes with sex‐specific expression based on comparisons with genome information for E. siliculosus can be performed using RNA‐seq data for female and male strains, without whole genome data, and can be applied to non‐model organisms (e.g., Shim et al . 2021; Nishitsuji et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the synchronization of nuclear division in G. monilis is regulated by Ca 2+ -mediated ROS signaling: a study of the woundhealing process in the same species showed that the hydrogen peroxide production induced by the intracellular calcium influx mediates wound healing, including the division of repair cells (Moon et al 2022). The same type of signaling has also been reported to mediate the fertilization process in other red algae (Shim et al 2021). Further studies are needed to determine whether Ca 2+ -mediated ROS signaling is also involved in the coordination of nuclear division in multinucleate cells.…”
Section: Merged Imagementioning
confidence: 98%
“…Studies of the function of the cytoskeletal component in red algae have mainly been carried out during fertilization (Shim et al 2020), as it is relatively easy for inhibitors to enter the reproductive cells. Actin has been shown to mediate the movement of spermatial nuclei within the trichogynes of several red algae during fertilization (Kim and Kim 1999, Wilson et al 2002, Shim et al 2021). However, investigations on the involvement of microtubules in various cellular responses in red algae have only recently begun (Moon et al 2022).…”
Section: Microtubule Stainingmentioning
confidence: 99%
“…Genetic diversity, speciation, and ecology have been documented within the Bostrychia genus (Karsten et al ., 1993; Zuccarello & West, 2011) where aspects of reproduction have also been investigated, including fertilisation (e.g. Pickett‐Heaps & West, 1998; Shim et al ., 2020) and haploid sex determination (Shim et al ., 2021). Finally, species within (or formerly attributed) to the Polysiphonia genus have been subjected to extensive electron microscopic studies in the past (Scott et al ., 1980; Delivopoulos & Kugrens, 1984) and are perhaps the most classic ‘textbook’ examples of red algae that are used to describe the ‘triphasic’ life cycle.…”
Section: Moving Towards a Red Macroalgal Model Systemmentioning
confidence: 99%